2002
DOI: 10.1038/sj.onc.1205605
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis: a powerful new tool for lung cancer diagnosis

Abstract: Carcinoma of the lung is the most common cause of cancer death worldwide. The estimated 5-year survival ranges from 6 -16%, depending on the cell type. The best opportunity for improving survival of lung cancer patients is through early detection, when curative surgical resection is possible. Although the subjects at increased risk for developing carcinoma of the lung (long-term smokers) can be identified, only 10 -20% of this group will ultimately develop the disease. Screening tests of long-term smokers empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
192
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(196 citation statements)
references
References 65 publications
1
192
0
3
Order By: Relevance
“…Methylation-based silencing of tumor suppressors is thought to be an important mechanism for gene inactivation and an early event in tumorigenesis (Belinsky et al, 1998;Nuovo et al, 1999;Baylin and Herman, 2000;Nephew, 2003). Consequently, genepromoter hypermethylation has become central to developing strategies for molecular screening, treatment and prognosis in a variety of cancers types (Tsou et al, 2002;Laird, 2003;Belinsky, 2004;Safar et al, 2005;Ushijima, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation-based silencing of tumor suppressors is thought to be an important mechanism for gene inactivation and an early event in tumorigenesis (Belinsky et al, 1998;Nuovo et al, 1999;Baylin and Herman, 2000;Nephew, 2003). Consequently, genepromoter hypermethylation has become central to developing strategies for molecular screening, treatment and prognosis in a variety of cancers types (Tsou et al, 2002;Laird, 2003;Belinsky, 2004;Safar et al, 2005;Ushijima, 2005).…”
mentioning
confidence: 99%
“…In lung cancer, the hypermethylation of CpG islands in promoter regions appears to be a common occurrence, as demonstrated by the analysis of genes from primary tumors, cell lines, patient sputum and serum (Rauch et al, 2008;Pfeifer and Rauch, 2009). Methylation 'signatures' with promising diagnostic and prognostic ability have emerged as potential biomarkers for lung cancer progression (Tsou et al, 2002;Belinsky, 2004;Safar et al, 2005). Safar et al (2005) identified the methylation of three genes as determinant of prognostic groups with varying 1-and 2-year survival rates (Safar et al, 2005).…”
mentioning
confidence: 99%
“…3 Histone deacetylation catalyzed by HDACs is the main histone modification in silenced gene promoters. 4 In cancer cells, several genes are silenced by alteration of the chromatin structure with or without DNA methylation, [5][6][7] suggesting the involvement of abnormal HDAC gene activity. 8,9 Mammalian HDACs consist of 2 groups, classical HDAC genes and the recently identified NAD-dependent SIRT family.…”
mentioning
confidence: 99%
“…In this respect, an enormous interest has been recently raised by the discovery that cancer cells release their DNA into the patient's bodily fluids and that cancer-specific signatures, like point mutations and DNA methylation errors, can be recognized in the circulating DNA by PCR-based technologies that are the core for the development of fast and accurate assay for the early detection of primary cancer or of their recurrence. [1][2][3][4][5] Furthermore, although the identification of DNA methylation markers predictive of the response to chemotherapy is just beginning, several studies have shown the association between specific methylation aberrations and the efficacy of chemotherapy in cancer patients. [6][7][8] Alteration of the methylation status of selected CpG-rich promoter sequences is an early event of cell transformation that influences gene expression and thus is a particularly promising cancer biomarker for early diagnosis (reviewed in Baylin and Herman, 9 Verma and Srivatsava, 10 and Esteller 11 ).…”
mentioning
confidence: 99%